Role Adaptive Management Ambidexterity : Construction Escalation of Small Business performance - Febri Elsa Aldelia; Rokhmad Budiyono; Siti Rochmah (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2021)
Abstract The growth of MSME business performance is a prerequisite for developing countries in improving the welfare of their people in the future. This study aims to investigate the ambidexterity adaptive management variable as a solution in realizing MSME business performance. Organizational learning and absorptive capacity become a panacea in improving business performance. The results of previous studies still leave a gap between organizational learning and absorption capacity in increasing business performance growth. so in this study offers a new idea as a solution in closing the gap from previous research. Adaptive management ambidexterity is the agility of the organization to adapt to the ever-changing business environment through learning adapted to the absorption capacity of MSME entrepreneurs. as a mediator of organizational learning and absorptive in improving MSME business performance. Myopia learning is learning to absorb experience and exploit other people's knowledge and explore their own knowledge, become a mediator of organizational learning and have a significant influence with adaptive management ambidexterity in spurring SME business growth. This research is very useful as a solution in solving the weaknesses of the organization's business performance, especially SMEs. The new concept of Adaptive Management Ambidexterity is used agilely and synergistically for the development of SME business performance, both internally and externally through myopia learning and absorption capacity. We suggest that the context of Adaptive Management Ambidexterity can be selected, tested and put into practice both theoretically and managerially, for future practice and research.